2020
DOI: 10.3390/jcm9072086
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Chairside Microbial Detection Predicts Endodontic Treatment Outcome

Abstract: Background. The aim of this longitudinal, one-year cohort study was to explore the hypothesis that fluorescence sampling of the root canal space prior to obturation could predict the outcome of root canal treatment (RCT). Methods. Sixty-five teeth underwent primary RCT and were followed up clinically and radiographically. The outcome was determined radiographically with periapical radiographs (PR) and cone beam computed tomography (CBCT) scans. Results. Success at 12 months was predictable based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…This increased sensitivity can result in the detection of apical periodontitis in cases where radiographic examination suggests complete resolution (strict criteria of success) or reveal enlarged lesions in cases where the reduction of the size of radiographic radiolucency (loose criteria of success) is considered. Despite Wu et al's call in 2009 for increased outcome reporting using CBCT imaging, in this updated review, only 4 of the 42 included studies used CBCT imaging for follow-up evaluation (Knight et al, 2020;Restrepo-Restrepo et al, 2019;Verma et al, 2020;Zavattini et al, 2020). For consistency, when both radiographic and CBCT outcomes were reported, only the outcomes based on radiographic evaluation were included for analysis in this review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased sensitivity can result in the detection of apical periodontitis in cases where radiographic examination suggests complete resolution (strict criteria of success) or reveal enlarged lesions in cases where the reduction of the size of radiographic radiolucency (loose criteria of success) is considered. Despite Wu et al's call in 2009 for increased outcome reporting using CBCT imaging, in this updated review, only 4 of the 42 included studies used CBCT imaging for follow-up evaluation (Knight et al, 2020;Restrepo-Restrepo et al, 2019;Verma et al, 2020;Zavattini et al, 2020). For consistency, when both radiographic and CBCT outcomes were reported, only the outcomes based on radiographic evaluation were included for analysis in this review.…”
Section: Discussionmentioning
confidence: 99%
“…For consistency, when both radiographic and CBCT outcomes were reported, only the outcomes based on radiographic evaluation were included for analysis in this review. Radiographic and CBCT outcomes were reported for 2 studies (Knight et al, 2020; Zavattini et al, 2020). For those studies, the success rates of CBCT analysis were lower than those reported after radiographic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the sampling technique, the use of a negative culture result to inform progress of treatment has a positive impact on treatment outcome. More recently, alternative bacterial tests, such as, fluorescent vital dye has been tested for use as a rapid chair-side root canal microbial detection method to predict periapical healing with promising results (Knight et al, 2020). The evidence shows the value of such a quality-control measure to return root canal treatment to a biological fold.…”
Section: F I G U R Ementioning
confidence: 99%
“…Other simple and potentially useful biomarker assays have been proposed in the form of rapid fluorescence tests in conjunction with paper points (Herzog et al, 2017 ). Pre‐commercial set‐ups have been used to check whether a root canal system is sufficiently decontaminated to be filled (Knight et al, 2020 ).…”
Section: Chairside Assays and Biosensorsmentioning
confidence: 99%